New Insights On Detecting Flaws With Csl And Tip - Andrew Z. Boeckelmann; David S. Graham; Paul J. Axtell (Deep Foundations Institute, 2022)
In the last fifteen years, several research studies have evaluated the ability to detect various types of deep foundation concrete integrity flaws with crosshole sonic logging (CSL) and thermal integrity profiling (TIP). This paper synthesizes the findings from the research, focusing on two studies that included CSL and TIP testing of drilled shafts with various types of flaws. The first, a 2016 research study of test shafts for the Wisconsin DOT, included inclusions inside and outside the reinforcing cage, intentional tremie withdrawal during concreting, and soft bottom flaws. The second, a 2021 study of production shafts for the Missouri DOT, included one shaft with and another without soft bottom conditions. After synthesizing the ability of each test method to detect each type of flaw, the paper presents recommendations for improving how CSL and TIP results are evaluated in practice. The recommendations highlight DFI‟s CSL interpretation protocol as well as the importance of evaluating TIP data versus time, not just depth. The paper includes example temperature-versus-time plots for various types of flaws and emphasizes how temperature-versus-time evaluation can be used to distinguish soft bottom conditions from standard bottom-of-shaft temperature roll off.